Emergence and Spread of the SARS-CoV-2 Omicron Variant in Alberta Communities Revealed by Wastewater Monitoring - Hubert, Casey R. J.; Acosta, Nicole; Waddell, Barbara J.; Hasing, Maria E.; Qiu, Yuanyuan; Fuzzen, Meghan; Harper, Nathanael B. J.; Bautista, María A.; Gao, Tiejun; Papparis, Chloe; Doorn, Jean V.; Du, Kristine; et al. (medRxiv, 2022)
Wastewater monitoring of SARS-CoV-2 allows for early detection and monitoring of COVID-19 burden in communities and can track specific variants of concern. Targeted assays enabled relative proportions of SARS-CoV-2 Omicron and Delta variants to be determined across 30 municipalities covering >75% of the province of Alberta (pop. 4.5M) in Canada, from November 2021 to January 2022. Larger cities like Calgary and Edmonton exhibited a more rapid emergence of Omicron relative to smaller and more remote municipalities. Notable exceptions were Banff, a small international resort town, and Fort McMurray, a more remote northern city with a large fly-in worker population. The integrated wastewater signal revealed that the Omicron variant represented close to 100% of SARS-CoV-2 burden prior to the observed increase in newly diagnosed clinical cases throughout Alberta, which peaked two weeks later. These findings demonstrate that wastewater monitoring offers early and reliable population-level results for establishing the extent and spread of emerging pathogens including SARS-CoV-2 variants. Alberta Health